AN ANALYSIS ON THE OUTCOME OF DEMONETIZATION IN INDIA-OPPORTUNITIES AND CHALLENGES - Dr. Sumanta Bhattacharya; Bhavneet Kaur Sachdev (International Engineering Journal For Research & Development, 2021)
Prime Minister Narendra Modi on 8th November , 2016 called for demonetisation with the aim to remove black money from the country , prevent crimes and make cashless transactions . This had more of a negative impact on the country’s economy , where the global economy was growing we say a decline in the growth rate of Indian economy , this demonetisation resulted in the lost of jobs and lakh and crore of money was lost . The agriculture sector was badly affected by the demonetisation where the whole business run on cash followed by small manufactures and even traders were affected . The demonetisation was followed by many terror attach in India , the motive was to stop terror funding , however the Demonetisation had a zero impact on terror funding and we see a rise in crimes like drug trafficking . Digital India and Digital Economy has been successful in some parts of the country , still a maximum rural area requires internet connectivity to start with the business of cashless transaction . people need to be educated on how to hand a bank account and the country needs to be made digitally educated , the informal sector has been badly affected and we have seen a decline in GDP growth over the years.